The Tatras – nappes and landscapes - Felisiak, Ireneusz (Geotourism/Geoturystyka, 2018)
Geological structure of the Tatra Mts is a result of long-lasting processes. The key nappes have already been completed some 65 Ma ago. However as a mountain range the Tatras has emerged at the surface only 5 Ma ago, when a piece of continental crust separated from African continent at the beginning of Mesozoic era ultimately collided with Europe. Thus, the crystalline core of the Tatras, which builts also the highest crest is a fragment of Africa. This monumental mountains are, however, not an effect of the overthrusting but they resulted from young, vertical tectonic movements, which are still active and which sometimes shake the whole Podhale region. The following paper explains how the Tatras were formed. The figures enclosed illustrate the succeeding formation stages of the mountain range and the photographs allow the Reader to compare drawings with the field. Welcome to the Tatras.//Struktura geologiczna Tatr formowała się bardzo długo, a kluczowe dla niej płaszczowiny były już gotowe przed 65 milionami lat. Pomimo tego jako góry Tatry zaczęły się wyraźnie zaznaczać na powierzchni dopiero 5 mln lat temu. Trzeba było aby kawał skorupy kontynentalnej, oderwany od Afryki z początkiem ery Mezozoicznej, ostatecznie wbił się w kontynent Europejski. Jego fragmentem, okruchem Afryki, jest trzon krystaliczny tworzący m. in. Tatry Wysokie. Ich imponujący wygląd nie jest wszakże efektem ruchów nasuwczych a młodych przesunięć pionowych, które do dziś czasami trzęsą Podhalem. Jak to się stało opisuje poniższy artykuł. Zamieszczone w nim rysunki ilustrują kolejne stadia rozwoju Tatr. Liczne zdjęcia pozwalają porównać papierowe konstrukcje z rzeczywistymi dziełami natury. Zapraszam do lektury i wycieczki w Tatry. Autor.